Model Kurikulum Pesantren Salafiyah dalam Perspektif Multikultural - Syafe'i, Imam (Universitas Islam Negeri Raden Intan Lampung, 2017)
Islamic boarding schools are one of the social religious institutions and Islamic education. In general, all pesantren must have characteristics that are not different, namely an institution whose leaders and caregivers are clerics. One type of boarding school in Indonesia is salafiyah boarding schools with special characteristics, namely salaf (traditional). The learning of classical Islamic books or often called